Investigating Ilami EFL Performance in Observing Within-Word Rules Based on Their Gender. (24th June 2015) - Rajabi, Malihe; Gowhary, Habib; Azizifar, Akbar
Abstract: Since in EFL contexts both teachers and students are less exposed to authentic language with a native pronunciation, presenting rules for standard American pronunciation appears to be overarching. Accordingly, providing both learners and teachers with an effective phonological profile is inevitable to achieve a standard American pronunciation. From among the hindrances to achieve a standard pronunciation lack of such a profile seems to be of critical importance. Considering lack of research on the foregoing obstacle in Iranian context, the present study aimed at presenting within-word rules of standard American pronunciation for Ilami EFL teachers in segmental phonology. The current study extracted, first, the within-word rules of standard American pronunciation from authentic sources. The profile developed in the study included 23 within-word rules. Additionally, the present study investigated the roles that might be played by Ilami EFL teachers' gender, in their observing of within-word rules developed in the study. Finally, the study determined if the phonological rules of within-word features of speech were affected by the gender of Ilami EFL teachers. To this end, among the accessible population in the study (all male and female EFL teachers in Ilam province), 40 teachers (20 males and 20 females) were randomly surveyed on interviews for their observing of 23 rules by reading a topically unrelated corpus. Chi-Square tests were conducted to analyze the data. Statistical analysis was run using Statistical Package for Social Sciences (SPSS). The results showed no significant relationship between the gender of Ilami EFL teachers and their observing of within-word rules.